The Role of Career Guidance Support in Shaping College Students' Career Motivation and Planning Behavior - Yang, Zhenzhen; Corbeta-Gomez, Serena; E. Borines, Marissa (Jurusan Pendidikan Teknik Elektro, 2025)
Objective: Against the backdrop of growing labor market uncertainty and the rising need for students' career self-management, this study aims to explore the longitudinal development trajectories of college students' career motivation and planning behaviors, and to analyze the predictive role of perceived career guidance support at different stages. Method: Drawing on the Situated Expectancy-Value Theory, a four-year longitudinal tracking survey was conducted on 812 undergraduates. Latent Growth Modeling (LGM) was employed to assess the dynamic changes in career expectancy, valuing, exploration, planning, and participation behaviors, while examining the initiating, sustaining, and contemporaneous effects of career guidance support. Results: All motivational and behavioral indicators showed a downward trend, with a sharp decline observed between the first and third years. Perceived career guidance support exerted three effects: it enhanced the initial levels of motivation and behavior (initiating effect), mitigated the decline in expectancy and exploration (sustaining effect), and significantly predicted concurrent outcomes at each stage (contemporaneous effect). Novelty: This study integrates motivational and contextual perspectives to reveal the stage-specific mechanisms of career support. It highlights the importance of early and continuous institutional intervention in curbing motivational decline, providing a theoretical basis for designing developmentally adaptive career guidance systems in higher education.